… And Starring David Foster Wallace as Himself: Performance and Persona in The Pale King. Issue 2 (14th March 2016) - Miley, Mike
ABSTRACT: When viewed alongside Wallace's interviews and publicity materials, multiple texts by Wallace— The Pale King, "My Appearance, " and the annotations in his personal library—present a different and deeper understanding of authorship and authenticity in contemporary literature. Taken together, these texts by and around Wallace portray the fiction writer more as the stage actor, a figure who is always in the process of presenting a persona, whether he or she knows it or not, to the extent that his or her private self becomes conflated with the inauthentic public persona. The Pale King appears to say that the fiction writer finds himself or herself in a Wallaceian double bind in which any sincerity to be achieved is possible only through the artificial means of performance.